The Effect of Health Education Simulation on First Aid on Students’ Knowledge Level - Sihombing, Roy Wilson Putra; Rahmani, Samaneh (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: The aim of this study was to analyze the influence of health education simulations about first aid on students’ level of knowledge. Methodology: This study used a pre-experimental research design with a one-group pre-post test design. The population was 11th-grade Science students. The sampling technique used was a total sampling of 45 students. A questionnaire was used to measure the students’ knowledge levels. Main Findings: Based on the Wilcoxon test, the p-value was 0.001 (p <0.05). This indicates that the health education simulation on first aid has an effect on students’ knowledge levels. Novelty/Originality of this study: This research can be used as a development of knowledge for junior high school students so that they know and are able to apply and simulate first aid at school.